Metabolomic profiling unravels divergent adaptive responses of oil palm (Elaeis guineensis) seedlings to drought stress under shaded and unshaded conditions - M. ADRIAN; RATNA WULANDARI; EDYSON SEMBIRING; AZIS NATAWIJAYA (Society for Indonesian Biodiversity, 2024)
Abstract. Adrian M, Wulandari R, Sembiring E, Natawijaya A. 2024. Metabolomic profiling unravels divergent adaptive responses of oil palm (Elaeis guineensis) seedlings to drought stress under shaded and unshaded conditions. Biodiversitas 25: 2404-2414. This research takes a unique approach by investigating the metabolomic responses of oil palm (Elaeis guineensis Jacq.) seedlings to drought stress under both shaded and unshaded conditions. Drought stress poses a significant threat to oil palm cultivation, with profound implications for global palm oil production. Our study aims to unravel the adaptive mechanisms of oil palm seedlings through metabolomic profiling, specifically focusing on amino acids and isoprenoids. The methodology involved collecting samples at distinct time points, including normal conditions, 7 days after drought stress (7 DAT), and 14 days after drought stress (14 DAT). Gas Chromatography-Mass Spectrometry (GC-MS) was used for comprehensive metabolite analysis. The results unveiled substantial changes in metabolite profiles, particularly in amino acids and isoprenoids, indicating the plant's concerted efforts to maintain biochemical homeostasis and vitality during drought stress. Cluster analysis revealed distinct metabolic responses between shaded and unshaded conditions, suggesting an initial conservative response followed by subsequent adaptive measures over time. The fold-change analysis identified key compounds such as Proline, Methyl Palmitate, and octadecylamine, which are crucial for the plant's adaptation to drought conditions. ROC analysis further confirmed Proline and D-Glucuronic Acid Amide as potential biomarkers for distinguishing plant responses to drought stress. This comprehensive metabolomic investigation provides valuable insights into the adaptive strategies employed by oil palm seedlings, thereby offering practical implications for developing sustainable cultivation practices and mitigating drought stress in oil palm cultivation.